The European Union as a normative power? : The extraterritorial reach of the EU’s personal data protection standards - Stehlíková, Jana; Zemanová, Štěpánka, 1975-; Druláková, Radka, 1973-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2022)
The dissertation thesis seeks an answer to the question of the EU’s normative power in the process of GDPR diffusion beyond the borders of European integration. The normative power is understood as a process of expanding the influence and power through the transfer of legal standards, values and legal culture, which can lead to a successful establishment of an international (sub)regime in the respective area. The three states selected for the empirical part of the thesis, Norway, Serbia and Ukraine, represent the countries with the highest probability (so-called most likely case studies) of the presence of EU normative power in their category. The categories are a member country of the European Economic Area, an EU candidate country and a party to an association agreement with the EU. In order to achieve the aims of the thesis, a matrix based on the constructivist approach in international relations and the theory of compliance was developed. The matrix builds on 11 criteria determining the current state of (pre-)preconditions for formal and behavioural compliance with the selected norm and nine factors that positively or negatively influence compliance achievement. From the methodological perspective, the thesis combines textual discourse analysis and process tracing. As the EU’s normative power was recognised only in one of the three examined countries (the case study of Norway), the findings lead to a conclusion that in the case of GDPR diffusion, the EU’s potential to establish an international sub-regime in the field of data protection cannot be proven.
Vedoucí práce: Štěpánka Zemanová
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: mezinárodní politické vztahy [obor disert. práce]; disertace; dissertations